Ergonomic Evaluation of the Risk of Suffering from Musculoskeletal Disorders in Nurses with Quick Exposure Check (QEC) and the Effect of 8-week selected Corrective Exercises and Ergonomic Occupational Intervention on their Exposure Rate - Raziye Karimian; Nader Rahnama; zeinab karimimoghaddam; Maryam Karimian; Azam Janbozorgi (Fasa University of Medical Sciences, 2015)
Background & Objective: In order to reduce work-related musculoskeletal disorders in ergonomic approach, all effective factors in occurrence of disorders, should be evaluated. This approach can provide an optimal solution for the omission or reduction of work-related musculoskeletal disorders. The aim of the present study is ergonomic evaluation of nurses' risk of suffering from musculoskeletal disorders with Quick Exposure Check(QEC) and the effect of 8-week selected corrective exercises and ergonomic occupational interventions on their exposure rate. Materials & Methods: Therefore, Nordic questionnaire and Quick Exposure Check of the factor risk were applied for 6 tasks of nurses.  Results: 85.7% of nurses reported occupation as the major factor for musculoskeletal disorders and 89% of nurses' tasks studied were in high or very high risk. There was a significant difference in care techniques used by nurses (P<0.05).  Moving up patients (87.7%) had the highest risk and giving drugs (66.2%), determining the vein (65.1%), dressing a wound, participation in visiting patients (59.9%), and reporting (51.1%) were in the following risk orders. After 8 week corrective exercises and ergonomic interventions there was a significant reduction in the risk rate of suffering from musculoskeletal disorders in 6 tasks by nurses (P<0.05 ). Conclusions: The results show that high risk level was a sign for susceptible conditions and workplaces in the hospital and corrective technique of moving up patients and improved conditions for moving up patients, improved other care techniques and selected corrective exercises reduced the risk level.